MODIFICATION OF THE SOCIALIST REALISTIC CANON OF UKRAINIAN LITERATURE: PROBLEM OF DEMYTHOLOGIZATION - Fedoriv, Ulyana (Porównania, 2019)
The XXI century demands from the modern literary criticism a revision of many strata of the Ukrainian culture that have been ignored for years. For a long time, the problem of Socialist Realism has belonged to the category of forgotten. Modern landmarks have changed. This is evidenced by the publication of a number of literary, cultural, sociological, anthropological studies of the Soviet times. The need to re-read and re-think socialist realistic literature is one of the key tasks in the field of topical objects of the scientific study in modern literary criticism. However, actively exploring this topic, there are still many ambiguous moments, including the problem of modification of the socialist realistic canon and the peculiarities of the process of its demythologization.